Analysis of Strategy for Local Beef Cattle Competitiveness Development in North Sulawesi - Jolanda. K.J. Kalangi; Jolyanis Lainawa; Anneke K. Rintjap (AIBPM Publisher, 2022)
Local beef cattle (Ongole Crossbreed) in North Sulawesi are still traditionally raised, making its product competitiveness is low. The purpose of this research is to describe the utilization of production factors increasing the competitiveness of livestock and meat commodities, conduct a feasibility study for its development, and formulate a strategy for developing its competitiveness. This qualitative-descriptive research is a case study model involving 160 respondents purposively selected as the sample. The analytical method was the feasibility test of investment criteria. The strategy formulation was divided into the input stage (to analyze internal and external factors), the matching stage (SWOT matrix and IE matrix), and the decision stage (with a Quantitative Strategy Planning Matrix). The findings indicate that the production factor resources were available with investment criteria requirement and strategic priority.